PENGARUH PERAN ORANG TUA TERHADAP MINAT BELAJAR PESERTA DIDIK DI MI AL ISTIQOMAH - Annanta Salsabilla; Maulidatur Rizkiah; Nova Diana Putri; Yusuf Aditya Rahman; Yulia Elfrida Yanty Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Students learning problems are very varied, such as not wanting to write, not being able to read, not doing assignments and homework. The aim of this research is to find out the role of parents in increasing the interest in learning of class students at MI Al Istiqomah. The method used in this research is a qualitative descriptive research method with data collection techniques using observation, interviews and field notes. In this study, researchers concluded that the role of parents in children's interest in learning has a big influence, especially if the learning process is carried out at home. Parents who help the school in delivering lesson material and completing daily assignments and tests act as motivators so that children are not lazy, so that their achievements will continue to grow and improve.